KOMPARASI HASIL BELAJAR MATEMATIKA PADA TINGKAT SEKOLAH DASAR MELALUI MODEL PEMBELAJARAN GROUP INVESTIGATION(GI) DAN MODEL PEMBELAJARAN KUMON - Nur Asrawati (Jurnal Pendidikan Dasar Borneo (Judikdas Borneo), 2020)
This research is aimed to compare the resulta of learning mathematich on the Six grade student of SD Panaikang III Makassar that is taught by using group investigation learning and kumon learning. This is an experimental research . the technique of collecting data was through the result of students written test. The result of the data was taken from descriptive and inverential analysis. The average of the descriptive analysis of the students’ result by using group investigation model (GI) was 76.52 in the high category, while the average of the students’ result that was taught by using kumon learning model was 34.52. it was in the lowest level. It was strengthened by the result of statistic  inferential analysis  = 14.750   = 1.676 and it was got that    , so is rejected and   is accepted and the students’ result of the six grade of SD Panaikang III Makassar that is taught by using grup investigation model is higher than kumon learning model.